RITE-DE-PASSAGE OF THE DEAD: WORLDVIEW OF THE ADIYAN OF WAYANAD, KERALA - M., Sini (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Adiyan is one of the tribal communities in Wayanad district of Kerala. They practice elaborate rituals and ceremonies and the death rituals reflect their worldview. Rite of passage is observed as a transition rite to mark the passing of a person from one state to another especially during the life course. The death rituals practiced by the Adiyan shows the separation and transition of spirit of a deceased from earth and its incorporation into another world, i.e., passage from one status of life to another and the rituals and ceremonies enable to change from one status to another.